THE OBSTACLES AND STUDENTS’ NEEDS: THE ANALYSIS IN LEARNING LISTENING FOR BEGINNER STUDENTS OF ENGLISH DEPARTMENT - Arin Arianti; Nurna ningsih (The Center for Language Development, Mataram State Islamic University., 2019)
Listening is one of English skills that require attention and understanding. It uses our ears to receive sounds and our brain to convert idea into meaningful messages. It is essential for lecturers to have overall understanding on what listening is, why it becomes difficult for foreign language learners. This study aims to describe the students’ needs based on the obstacles faced by students in learning literal listening. Qualitative method was used in the study. The subjects of this study were first semester students of English Department in Veteran Bangun Nusantara University of Sukoharjo. The data was taken by observation, interview, and questionnaire. The findings show that beginner students need to enrich various listening texts in different context to gain information from many kinds of genres. It was related to listening problems faced by students. Lack of vocabulary and how words pronounced and also recognizing main points become obstacles for students in listening activities. Moreover, the ways of teacher to handle those needs must be more creative in providing materials and utilizing the technology equipment.